2010
DOI: 10.1007/s10344-010-0374-0
|View full text |Cite
|
Sign up to set email alerts
|

The good bad wolf—wolf evaluation reveals the roots of the Finnish wolf conflict

Abstract: This article focuses on the roots of the Finnish wolf conflict by using stakeholder evaluations of the wolf as a tool. The recent growth of the wolf population has highlighted stakeholders_ contradictory objectives and revealed a conflict between the two main stakeholders, conservationists and hunters, in wolf management. The question of hunting emerges as the core of the conflict. The negative evaluation of the wolf by hunters reflects a competitive situation, which is typical of the historical development of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 13 publications
2
47
1
Order By: Relevance
“…The coding scheme for the analysis clustered hunters' experiences of their perceived persecution at the hands of the state, local state agencies and other Environmental Non-Governmental Organisations (ENGO) they accused of being powerful lobbyists, agenda-setters and ultimately persecutors in the current wildlife conservation regime in Sweden. The findings from interviews strongly cohere with concurrent empirical findings about hunters from Norway and Finland (Bisi et al 2010;Krange and Skogen 2011;Linnell 2013;Risvoll, Fedreheim and Galafassi 2016). Hunters' reflections are presented phenomenologically in line with the research's objectives, meaning that we understand their claims and experiences of persecution as a priori truthful.…”
Section: Methodssupporting
confidence: 65%
“…The coding scheme for the analysis clustered hunters' experiences of their perceived persecution at the hands of the state, local state agencies and other Environmental Non-Governmental Organisations (ENGO) they accused of being powerful lobbyists, agenda-setters and ultimately persecutors in the current wildlife conservation regime in Sweden. The findings from interviews strongly cohere with concurrent empirical findings about hunters from Norway and Finland (Bisi et al 2010;Krange and Skogen 2011;Linnell 2013;Risvoll, Fedreheim and Galafassi 2016). Hunters' reflections are presented phenomenologically in line with the research's objectives, meaning that we understand their claims and experiences of persecution as a priori truthful.…”
Section: Methodssupporting
confidence: 65%
“…In general, people in rural areas perceive wolves as a negative influence, a traditional enemy to rural culture that limits day-to-day activities [2]. Avoiding wolves is also often seen as necessity in order to perceive rural culture: both in a sense of maintaining traditional rural industry and defending political autonomy against urban interests [12,13].…”
Section: Political Alienation and Collective Level Effectsmentioning
confidence: 99%
“…Proximity to wolves [7] and direct experiences with wolves [5] have been found to make people less positive towards wolves, and thus growing wolf populations are likely to increase the attitude divide between urban and rural people over time [8]. Living close to wolves means reduced opportunities to hunt and a heightened fear for the safety of dogs, livestock, and people [2,8]; thus, wolf presence has a negative impact on attitudes towards wolves and wolf policy. The demographic structure of rural areas in Sweden further reinforces the attitude differences between rural and urban people, as factors more common among the Swedish rural population, such as hunting, a lower education level, old age, and being male, have been found to correlate with less positive attitudes towards wolves [1,5,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to hunters' attitudes these studies arrive at different conclusions. Many studies have identified an association between hunting and negative attitudes towards large carnivores (Zeiler et al 1999, Naughton-Treves et al 2003, Ericsson et al 2004, Karlsson and Sjöström 2007, Bisi et al 2010). Yet other research has shown that hunters do not generally hold negative attitudes towards large carnivores and can even be more supportive than non-hunters (Bjerke et al 1998, Williams et al 2002, Ericsson and Heberlein 2003, Kaczensky et al 2004, Bath et al 2008.…”
mentioning
confidence: 99%